Prevalence, Awareness, Treatment, and Control of Hypertension and Diabetes: Results From Two State-Wide STEPS Survey in Punjab and Haryana, India - Thakur, J. S.; Nangia, Ria (Frontiers in Public Health, 2022)
India which is home to more than one-sixth of the world's population accounts for more than two-thirds of total deaths due to non-communicable diseases(NCD). Out of this, hypertension and diabetes are the most common NCDs. Awareness, treatment, and control of hypertension and diabetes remain a major challenge despite various national programs being operational to curb the rising burden of NCDs. In order to fill the knowledge gap, these rates were studied among the adult population in two major northern Indian states of Punjab and Haryana. Two state-wide NCD risk factors surveys were conducted using WHO STEPS methodology among 5127 individuals in Punjab and 5078 individuals in Haryana aged 18-69 years. A standardized questionnaire was used to determine the behavioral risk factors in step 1followed by anthropometric measurements for physical risk factors in step 2 and in step 3 serum and urine samples were collected for biochemical risk factors. The prevalence of hypertension in Punjab was 40.1% while that in Haryana was 26.2%. In Punjab, 48.3% of the hypertensives were aware of their condition, 30.9% were on treatment while 18.3% of the cases were controlled. While in Haryana 33.4% of them were aware of their condition, 26.3% are on treatment while 12% of the cases were controlled. Similarly, the prevalence of diabetes was 14.3% and 15.1% in Punjab and Haryana respectively. In Punjab 34.2% of diabetics were aware of their condition, 28.2% were on treatment while only 14.2% of the cases were controlled. In Haryana 29.5% of them were aware of their condition, 22.4% were on treatment while only 13.8% of the cases of diabetes were controlled. Family history of diabetes and hypertension was found to be associated with higher odds of being aware and controlled blood glucose and blood pressure levels in both Punjab and Haryana. Hypertension and diabetes are major public health problems in Punjab and Haryana and awareness, treatment, and control rates are low which require specific interventions with a focus on access to treatment, regular follow-up for better control. There is an urgent need to effectively implement the existing national NCD programs in these states in India.